Prevalencia de violencia de género en mujeres del cantón Catamayo - Pauta Pauta, Jordy Paul (2023)
Gender violence against women is currently considered a public health problem, which attacks the development of societies by not respecting human rights. In this way, the WHO estimates that one in three women is a victim of acts of violence, whether physical or psychological. In the province of Loja, the Catamayo canton is one of the cantons with the highest rate of violent acts against women. The objective of this research was to determine the prevalence of gender violence in the Catamayo canton. It had a descriptive and cross-sectional approach, where convenience sampling was used with a sample of 150 people to whom the surveys were applied, from a population made up of 13,672 women (data extracted from the recent census carried out by the National Institute of Statistics and Censuses during the period 2010). A survey was applied focused on verifying whether or not violence exists, socio-demographically characterize and visualize the situation of women who suffer gender violence. The results showed that 23% of women in the Catamayo canton suffer gender violence. In this way, it is concluded that there is a significant prevalence of this public health problem in said canton, with the home being the place where these acts of violence against women occur most frequently. Furthermore, this corroborates that there is still patriarchal thinking in our society that causes human rights to be violated, which is why the Ministry of Public Health, together with other institutions, has to promote preventive actions in order to guarantee comprehensive care and timely for women who suffer gender violence